System criminality in international law - Wilt, Harmen van der, 1955-; Nollkaemper, André.; Dolman, M. M. (Menno M.); Kleffner, Jann K. (Cambridge, UK ; New York : Cambridge University Press, 2009)
How does international law respond to situations where collective entities order, encourage or allow the committing of international crimes?
Introduction / André Nollkaemper -- The policy context of international crimes / Herbert C. Kelman -- Why corporations kill and get away with it : the failure of law to cope with crime in organizations / Maurice Punch -- Men and abstract entities : individual responsibility and collective guilt in international criminal law / Gerry Simpson -- A historical perspective : from collective to individual responsibility and back / Andrea Gattini -- Command responsibility and Organisationsherrschaft : ways of attributing international crimes to the 'most responsible' / Kai Ambos -- Joint criminal enterprise and functional perpetration / Harmen van der Wilt -- System criminality at the ICTY / Elies van Sliedregt -- Criminality of organizations under international law / Nina H.B. Jørgensen -- Criminality of organizations : lessons from domestic law : a comparative perspective / Albin Eser in cooperation with Felix Rettenmaier -- The collective accountability of organized armed groups for system crimes / Jann K. Kleffner -- Assumptions and presuppositions : state responsibility for system crimes / Iain Scobbie -- State responsibility for international crimes / A. Zimmermann and M. Teichmann -- Responses of political organs to crimes by states / Nigel D. White -- Conclusions and outlook / André Nollkaemper and Harmen van der Wilt.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Criminal jurisdiction; International crimes; Droit pénal international; Droit international pénal.; LAW -- Criminal Law -- General; Criminal jurisdiction; International crimes; State crimes; International crimes; Criminal liability; Collective responsibility; Individual responsibility; International responsibility